3 - China and Africa: Human Rights Perspective - Osondu-Oti, Adaora (Africa Development, 2021)
At the turn of the twenty-first century, China emerged as a major player in Africa’s international relations. This emergence has attracted a lot of attention in literature on what it portends for Africa. Studies have pointed that China’s involvement in Africa undermines human rights. Of important note was China’s support for the Sudanese government even in the face of human rights abuses; its unconditional aid to Angola, that has helped the government to shun accountability and transparency; its support for inhuman practices meted to the citizens of Zimbabwe by the government, among others. Against this background, this paper seeks to examine, in detail, current China-Africa relations from the human rights perspective. It intends to explore China and human rights in Africa and China’s stance on human rights issues. Another important aspect that is mostly ignored in literature is non-classification of those rights that China undermines in Africa. Is it civil and political rights, economic rights or both? This paper seeks to analyse all these in a bid to provide answers.